Construção e calibração de um inclinômetro para uso em tratores agrícolas como instrumento de segurança - Leite, Fabricio [UNESP]; Santos, Joao Eduardo Guarnetti dos [UNESP]; Lanças, Kleber Pereira [UNESP] (EIA Energy in Agriculture, 2010)
The tractors are the main potency source, for the traction of tillage equipments and their use are increasing more and more in Brazilian agriculture. In spite of the great technological progress the increase of the number of agricultural tractors brought positive aspects and some negative, among these last ones it stands out the appearance of a new source of work accidents, which importance is given by the physical damages caused to the operator. Therefore the objective of this work was to project and develop an inclinometer, which indicates the inclination of the land, as safety sensor for agricultural tractors to avoid lateral hollovers, through a resonant sign, for the operator and the machine preservation. The built and evaluated inclinometer showed to be efficient for inclination indication of different areas during field operations with agricultural tractors, small angle oscillation and enough answer time to help operators to take decisions in imminence situation of lateral machine hollovers.

Os tratores como fonte de potência, para o tracionamento e/ou acionamento de máquinas e implementos agrícolas dão origem a conjuntos motomecanizados, os quais têm sido utilizados de forma crescente na agricultura brasileira. Apesar do grande avanço tecnológico, o aumento do número de tratores agrícolas trouxe aspectos positivos e alguns negativos, entre estes últimos, destaca-se o surgimento de uma nova fonte de acidentes de trabalho, cuja importância é dada pelos danos físicos que causam ao operador. Portanto, o objetivo deste trabalho foi projetar, desenvolver e calibrar um inclinômetro, o qual indicava a inclinação do terreno, como sensor de segurança para tratores agrícolas com o intuito de evitar tombamentos laterais, para a preservação do operador e da máquina. O inclinômetro construído e avaliado mostrou-se eficiente para indicação da inclinação do terreno em operações de campo com tratores agrícolas, com pequena oscilação do ângulo e tempo de resposta suficiente para a tomada de decisão do operador em situação de iminência de tombamento lateral da máquina.
Construction and calibration of an inclinometer to use in agricultural tractors as safety instrument
Keywords: Lateral hollovers; Machine; Safety agricultural; Tombamento lateral; Máquinas; Segurança agrícola